Analysis Of The Effect Of Frequency Decrease On Performance On Five Phase Induction Motor - Suranta Sitorus (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2021)
Almost 70% of the energy produced by the generator is consumed by electric motors. The use of induction motors in industry and factories is more profitable than DC or synchronous motors, one of the advantages is easy maintenance and high efficiency. On machines in the industry speed regulation is absolutely necessary. Along with the development of power electronics, this has become very easy to do, namely by supplying a motor with a variable speed drive (VSD) inverter. With the supply of a variable speed drive inverter, it is possible to adjust the motor speed by adjusting the voltage frequency.This study was conducted to determine the effect of decreasing the frequency using a variable speed drive inverter on the performance of a five-phase induction motor. Tests are carried out at a frequency of 50 Hz (grid frequency), 35, 40, 45, 50 Hz (inverter frequency) and the motor is loaded at 0.5, 1, 1.5, 2, 2.5Nm. From the research, it was concluded that, among others, the use of a variable speed drive inverter resulted in greater motor losses and the motor produced a louder sound. At the same frequency (50 Hz) the efficiency of the motor is better when supplied directly from the grid.